(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
In this paper, we study countable β-compactness and present another new class of com pactness in ideal topological space via countable βρI-compact spaces by utilizing the notion of β-open sets. We also properties investigate some other of countable βρI-com pactness using different types of functions.